Subordination Method for the Estimation of Certain Subclass of Analytic Functions Defined by the q-Derivative Operator - Hormoz Rahmatan; Ali Shokri; Hijaz Ahmad; Thongchai Botmart (Journal of Function Spaces)
In this paper, we investigate an interesting class of analytic and biunivalent functions in the open unit disk Δ which is defined using the q-derivative operator. We apply the subordination method to the functional of coefficients problem. Furthermore, we obtain the bounds of the certain functional of coefficients for functions in the class HΣqλ,β, for real and complex parameters. Also, an estimation for the initial Taylor and Maclaurin coefficients of functions in HΣqλ,α was given.